ANALISIS PERMINTAAN ENERGI LISTRIK PADA INDUSTRI MEBEL DI KOTA PEKANBARU - Chalid, Nursiah; ', Permansyah; ', Taryono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to determine the effect of the furniture industry costumers and the value of production of the electric energy demand in the furniture industry in Pekanbaru and to determine the most dominant variable affecting the demand for electrical energy on the furniture industry in the City of Pekanbaru, Riau. The analysis of the data used in this research is quantitative deskriptive model of multiple linear regression model. Result of this study were obtained from questioner (primary) and some observations and direct interviews with respondents furniture industry which includes the identity of the respondent, the number of customer industries of furniture and furniture industry production value. The results showed that the adjusted R -square value of 0.823, which means that 82.3 % of electric energy demand in the furniture industry is influenced jointly by the variables in the model. While the remaining 17.7 % is influenced by other factors in the model. partial variable number of subscribers furniture industry ( X1 ) and the production value ( X2 ), significantly influence the dependent variable is the electrical energy demand in industry in the city of Pekanbaru ( Y ).Keywords : Electrical Energy Demand, Customer Furniture and Production Value